Is the presence of Helicobacter pylori in the Dental Plaque of Patients with Chronic Periodontitis a Risk Factor for Gastric Infection? - Mohammed Al Asqah; Nawaf Al Hamoudi; Sukumaran Anil; Abdulrahman Al jebreen; Waleed Khalid Al-hamoudi (Canadian Journal of Gastroenterology)
BACKGROUND: Helicobacter pylori is considered to be a pathogen responsible for gastritis and peptic ulcers, and a risk factor for gastric cancer. A periodontal pocket in the teeth of individuals with chronic periodontitis may function as a reservoir for H pylori.